The Use of Youtube Video to Improve Students’ Speaking Skill of Class VII UPTD SMP Negeri 22 Barru - Sukma, Sukma; Nur, Rafi’ah; Ammade, Salasiah; Latifa, Ammang; Larekeng, Siti Hajar (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The use of YouTube videos as a learning tool has the potential to enhance students' speaking skills. This study aims to determine whether incorporating YouTube videos into the curriculum can improve the speaking skills of seventh-grade students at UPTD SMP Negeri 22 Barru. This research was conducted using a pre-experimental method, with a one-group pre-test and post-test design. The research population consisted of seventh-grade students at UPTD SMP Negeri 22 Barru, with a sample of 27 students from class VII-2 selected through random sampling. The results of the study indicated that after the treatment, most students found learning English less difficult, particularly in terms of speaking skills. They began to feel more confident speaking in English and showed a higher enthusiasm for continuing to learn the language. This is supported by data showing that the mean pre-test score was 56.48, while the mean post-test score was 80. Additionally, the post-test mean score of 80 was higher than the minimum passing score of 75 at UPTD SMP Negeri 22 Barru. The result of the t-test score in the final test was 2.665, compared to a t-table value of 1.706. Therefore, the researchers conclude that the use of YouTube videos can improve the speaking skills of seventh-grade students at UPTD SMP Negeri 22 Barru.